An innervated skin 3D in vitro model for dermatological research - Rousi Emma; Malheiro Afonso; Harichandan Abhishek; Mohren Ronny; Lourenço Ana Filipa; Mota Carlos; Cillero-Pastor Berta; Wieringa Paul; Moroni Lorenzo (Switzerland, 2025)
A 3D in vitro model of innervated skin would be a useful tool in dermatological research to study the effect of different chemicals and compounds on the sensory properties of skin. Current innervated skin models are limited in composition and often composed of ex vivo skin explants and/or animal-derived material. In this study, our aim was to develop a human innervated skin model with a better biomimicry composition for in vitro research. Fibrin hydrogel and aligned electrospun fibers of poly(ethylene oxide terephthalate)/poly(butylene terephthalate) (PEOT/PBT) were used as a scaffold to generate the 3D in vitro model. The skin component was made of primary human keratinocytes and primary human fibroblasts, while the neuronal component was composed of iPSC-derived sensory neurons. Our results showed that the dermal component consisted of fibroblasts and synthesized collagen. The epidermal component was characterized by the expression of keratins 10 and 14, and involucrin. Finally, sensory neurons extended axons throughout the scaffold and reached the epidermis. Treating the model with a capsaicin solution for 30 min, which was performed as a proof of concept test for sensitization studies, resulted into partial depletion of substance P and tubulin β3. This model could be used for studying skin-neuron interactions and cutaneous toxicity.